2008
DOI: 10.1080/00952990701653867
|View full text |Cite
|
Sign up to set email alerts
|

Societal Perception and Support for Methadone Maintenance Treatment in a Chinese Province with High HIV Prevalence

Abstract: Methadone maintenance treatment (MMT) was first piloted in April 2004 in Yunnan, China, to reduce HIV transmission. This study aimed to examine public support for MMT and was based on cross-sectional data collected in March-April 2006 on a random sample of 411 police staff, medical/health professionals, community members, and drug users. Multivariate logistic regressions were used to analyze the data. The support was the strongest amongst the police and medical professionals but the lowest in drug users. A con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…These suggestions took many forms: providing general explanations of MMT, working with community leaders, and linking MMT to other services. Other studies have found levels of awareness and understanding among IDUs regarding the availability and benefits of harm reduction as a strong determinant of participation (Philbin et al, 2008;Tkatchenko-Schmidt et al, 2008;Yang et al, 2008). Some drug users and NGO members stated support for total abstinence.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…These suggestions took many forms: providing general explanations of MMT, working with community leaders, and linking MMT to other services. Other studies have found levels of awareness and understanding among IDUs regarding the availability and benefits of harm reduction as a strong determinant of participation (Philbin et al, 2008;Tkatchenko-Schmidt et al, 2008;Yang et al, 2008). Some drug users and NGO members stated support for total abstinence.…”
Section: Discussionmentioning
confidence: 93%
“…Studies report concerns among IDUs that utilizing harm reduction services would lead to the discovery of their status, resulting in increased stigma and prosecution by local police (Hammett et al, 2005b;Lu, Zhao, Bao, & Shi, 2008;Tkatchenko-Schmidt et al, 2008;Yang et al, 2008). Specific numbers of arrests are difficult to determine, but reports suggest that 10Á30% of IDUs spend time in a detoxification center each year (Reid & Costigan, 2002).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, the findings suggest that, aside from routine treatments, MMT clinical staff might offer more comprehensive interventions for patients and their family members, friends, and/or significant others, such as health education or counseling, family support training, and MMT knowledge lectures, all of which can be useful for establishing an accurate understanding of MMT among patients and reducing negative attitudes toward MMT patients among family members, and perhaps, society at large. Yang et al [45] concluded that dissemination of more accurate MMT knowledge and resolution of conflicting perspectives of MMT are urgently needed to increase societal support for MMT patients. With sufficient support received from society, patients’ perceived support would likely demonstrate a corresponding increase, thereby helping improve their HRQoL during long-term MMT.…”
Section: Discussionmentioning
confidence: 99%